The 1998 CCP directory and guide performing arts groups and arts councils in the Philippines. (Sentrong Pangkultura ng Pilipinas, 1998)
A very colorful book which contains a comprehensive profile of the Philippines' top performing groups as well as relevant information on the arts councils. It also has a directory of performing venues with rates and capacity.